ANALYSIS OF CANVA PUZZLE MEDIA NEEDS IN INDONESIAN LANGUAGE LEARNING FOR ELEMENTARY SCHOOL GRADE III - Vera Juniar; Herlina Usman; Mahmud Yunus (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This study aims to develop Canva-based puzzle media for Indonesian language subjects for third-grade elementary school students using the Research and Development (R&D) method of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), but this study is limited to the development stage, so the resulting product has not yet reached the stage of implementation and comprehensive evaluation in the field. Data collection was carried out through observation, student questionnaires, and teacher interviews which showed that 74.1% of students liked Indonesian language subjects, but 55.6% found it difficult, 92.6% of students wanted more creative learning, and 51.9% were more enthusiastic about game methods. The conclusion of this study is that Canva-based puzzle media is expected to increase students' interest in learning and active participation, while providing practical solutions for teachers in overcoming low interest in learning and enriching digital learning media references. Keywords: Puzzle Media, Elementary School